Block and malleable arsenopyrite hot-pressure sintering: applied implications - Kai Zheng; Heping Li; Shuai Wang; Luying Wang; Qingyou Liu (Journal of Materials Research and Technology, 2020)
A hot-pressure technique was used to sinter block-shaped, malleable, and compact arsenopyrite, based on the purified natural material. The results show that 500 °C and 1.0 GPa are the optimum temperature and pressure conditions, while at temperatures below 500 °C the product would become powdery or present visible cracks. Electron probe analysis (EPMA), X-ray diffraction (XRD), and Raman tests confirmed the purity of the samples with a molecular formula of Fe1.00As1.02S1.03. The calculated density was 6.2185 ± 0.0132 g/cm3, close to the unit cell density of 6.2389 g/cm3. The sample can easily be machined in a circular truncated cone shape, and used as an autoclave stopper at 440 °C and above 40 MPa for 35 h. Sintering results provide a possibility for further research on the electrochemical corrosion of sulfide minerals at high temperature and pressure. The hot-pressure procedure developed here provides a reference and inspiration for sintering other similar samples in this field.